Classification of human failure in chemical plants: Case study of various types of chemical accidents in south korea from 2010 to 2017 - Jung, Seungho; Pak, Seungkyoo; Lee, Kwanwoo; Kang, Chankyu (International Journal of Environmental Research and Public Health, 2021)
The increasing use and distribution of chemicals are causing serious chemical accidents such as fires, explosions, and leaks during manufacturing and handling. In most cases, all risks caused by chemicals are classified as accidents due to defects in process facilities, human errors, and multi-cause accidents. Among chemical accidents caused by human errors, accurate analysis of accidents caused by the complex action of various types of human failures is required. Based on the accident investigation reports that occurred in South Korea from 2010 to 2017, chemical accidents caused by human failure were analyzed, and the fundamental causes were derived by classifying them into human error and violation. Human failure was analyzed according to the classification criteria for human failure of health and safety executive (HSE). As a result of the analysis, several types of human failure acted in combination to be a more significant cause of chemical accidents; incorrect application of process rules and procedures, inappropriate chemical information, lack of education, and defects in the current safety regulation were analyzed as the main causes. In addition, the cause of human errors was presented through case studies of chemical accidents in South Korea.
Keywords: Accidents; Accidents, Occupational; Chemical Hazard Release; Fires; Humans; Republic of Korea; Chemical accident; Classification; HSE; Human failure; MSDS; RCA